A gestão nas Instituições de Ensino de Educação Básica: as escolas da Rede La Salle do Rio Grande do Sul - Dalvit, Olavo José (Universidade do Vale do Rio do Sinos, 2007)
This dissertation intends to present a study about the process change that the private education institutions have undergone in the last years, in special the La Salle schools of RS state, Brazil. Having as scenery the change process in the organizations the research shows how educational management has undergone this process in the last years and the impact that this change had in the Brazilian educational institutions. Specially and as object of study it is analyzed the process undergone by 11 schools of basic education of La Salle Net, located in the great Porto Alegre and in the interior of RS state. How those institutions welcomed and they adapted themselves to the changes, how the organizational atmosphere interfered in their changes and the leaderships’ paper in the process are some of the questions that this study tries to answer. The educational management inserts itself in a competitive atmosphere and it is part of the organizational management with its own characteristics of educational environment
Keywords: mudança organizacional; gestão educacional; organizational change; educational management; Ciências Sociais Aplicadas